Lycorine Derivative LY-55 Inhibits EV71 and CVA16 Replication Through Downregulating Autophagy - Wang, Huiqiang; Guo, Tingting; Yang, Yajun; Yu, Lian; Pan, Xiandao; Li, Yuhuan (Frontiers in Cellular and Infection Microbiology, 2019)
Hand, foot, and mouth disease (HFMD) is a global health concern, especially in the Asia-Pacific region. HFMD caused by Enterovirus 71 (EV71) and Coxsackievirus A16 (CVA16) infection is usually self-limited but occasionally leads to severe pulmonary edema, neurological complications, and even death. Unfortunately, no effective drugs are currently available in clinical practice for the prevention and treatment of HFMD. Thus, anti-HFMD drugs must be urgently developed. A previous study had reported that lycorine could inhibit EV71 replication. In the present study, we found that LY-55, a lycorine derivative, inhibited the replication of EV71 and CVA16 in vitro and provided partial protection to mice from EV71 infection, as indicated by the decreased viral load and protein expression levels in muscles, clinical scores, and increased survival rates of infected mice. Mechanistically, LY-55 was not directly viricidal. Instead, the LY-55-mediated inhibition of EV71 and CVA16 was found to be mechanistically possible, at least in part, through downregulating autophagy, which plays an important role for EV71 and CVA16 replication. These findings suggest that LY-55 could be a potential lead or supplement for the development of anti-HFMD agents in the future.